Текстовые соответствия русского модального слова конечно в английском языке - Puk, Maria (Acta Neophilologica, 2019)
This article analyzes the Russian modal exponent конечно expressing the speaker’s commitment to the truth of the proposition and its English translational equivalents. Some of the equivalents lower the level of epistemic modality, e.g., possibly, perhapsand might convey possibility and most probably, I suppose, I expect and I bet denote probability. Owing to such translational solutions, the translated sentences evoke a dif- ferent set of associations in the target language. The sentences with the omitted marker of epistemic modality constitute a great number of examples in English.